AAC don Ghaeilge': A needs analysis survey for the development of Irish language augmentative communication devices for people with speech difficulties.' - Nic Corcráin, Muireann (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2022)
Augmentative and alternative communication (AAC) systems, device development and research continues to emerge and develop, while all the time broadening to be more inclusive for those who utilise these systems to communicate effectively. With the focus on bilingual AAC and minority languages AAC development growing, the possibility of developing and optimising AAC technology for the Irish language continues to come to the forefront of developing inclusive and accessible ways to communicate in Ireland's first national language. A needs analysis survey was conducted to gain insight into what key features would be necessary for Irish AAC (bilingual, layout, high-tech or low-tech) and why such technology is in demand by those who wish to communicate in Irish, as an L2 learner or as members of the Irish-speaking community. Results indicate an interest into the development of Irish language based AAC technology. Key recommendations include integrating Irish text-to-speech synthesis into the AAC system, along with significant interest in a keyboard with Irish diacritics and the opportunity for users to model their own phrases. Other recommendations include working with Speech and Language Therapists to help address the lack of AAC assessment available through the medium of Irish. Future research into developing Irish AAC and trialling it in various demographics in society will shape and mould the research in the near future.
Keywords: AAC; Irish language; Assistive Technology